Pengaruh Kompetensi, Pengembangan Karir, Budaya Organisasi Dan Keadilan Organisasi Terhadap Kinerja Karyawan (PT Blue Ocean Heart Kantor Cabang Kediri) - Prayoga, Dhimas Enggal; Susyanti, Jeni; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was marked by a significant reduction in employees in the last 3 years from 450 employees to 250 employees. So with this phenomenon, I, as a researcher who has worked in this field, am interested in researching this problem. According to my observations, employee reductions occur due to employees' lack of understanding of competency, career development, organizational culture and organizational justice. The purpose of this research is to determine the influence of competency, career development, organizational culture, and organizational justice on employee performance.The research that will be used is explanatory research which is included in the quantitative method. Explanatory research is research that intends to explain the position of the variables studied and the relationship between one variable and another variable. The respondents in this research were 75 marketing employees. The sampling technique was purposive sampling for PT Blue Ocean Heart employees. The results of this research reveal that the influence of competence, career development, organizational culture, and organizational justice have a significant effect on employee performance. Keywords: Competency, Career Development, Organizational Culture, Organizational Justice, Employee Performance.